2005
DOI: 10.1302/0301-620x.87b11.16354
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of infection with the use of non-irradiated morcellised allograft bone washed at the time of revision arthroplasty of the hip

Abstract: Implantation of allograft bone is an integral part of revision surgery of the hip. One major concern with its use is the risk of transmission of infective agents. There are a number of methods of processing allograft bone in order to reduce this risk. One method requires washing the tissue using pulsed irrigation immediately before implantation. We report the incidence of deep bacterial infection in 138 patients (144 revision hip arthroplasties) who had undergone implantation of allograft bone. The bone used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…This result is consistent with previous results regarding bone graft contamination. 4,6 However, postoperative spinal infections were not associated with specific microorganisms. The presence of some of the infectious microorganisms, such as Pseudomonas or Propionibacterium species, was attributed to simple contamination during bone preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous results regarding bone graft contamination. 4,6 However, postoperative spinal infections were not associated with specific microorganisms. The presence of some of the infectious microorganisms, such as Pseudomonas or Propionibacterium species, was attributed to simple contamination during bone preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, absence of postoperative infection was defined as absence of any infectious signs or symptoms during the 1-year postoperative period. At each outpatient clinic visit (1,3,6, and 12 months after surgery), evidence of infection was actively sought. This involved obtaining a history of pain, inspecting the wound, and monitoring for radiographic changes.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Mechanical methods to remove blood and marrow contents from bone allograft have been shown to reduce bacterial contamination (Hirn et al 2001). Kwong et al (2005) have shown a bacterial infection rate of less than 1% when using unprocessed bone allograft washed at the time of surgery prior to impaction grafting (Kwong et al 2005). Washing may also help to reduce the risk of viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated improved shear resistance of washed specimens on mechanical testing (Dunlop et al 2003). Washing has also been shown to reduce the rates of bacterial infection (Kwong et al 2005) as well as the transmission of blood borne viruses such as Human Immunodeficiency Virus (HIV) (Simonds 1993) and Hepatitis-C Virus (HCV) (Conrad et al 1995) through removal of blood and marrow contents. What remains unclear at the present time is whether bone allografts can transmit prion diseases such as variant Creutzfeld-Jakob Disease (vCJD).…”
Section: Introductionmentioning
confidence: 99%
“…For the use of allograft, there still remains the latent risk of infection with unidentifi ed micro-organisms. 5,6 The use of a new form of artifi cial bone such as hydroxyapatite is a recent phenomenon, but the incorporation of the granules of hydroxyapatite may need a longer period when compared with auto-bone grafting. 7,8 To avoid the use of allograft and artifi cial bone, we performed total hip arthroplasty using the non-cement impaction auto-bone-grafting method with the resected femoral head for acetabular protrusion that is not combined with the destruction of the acetabular rim or dysplasia of the hip joint.…”
Section: Introductionmentioning
confidence: 99%